2020
DOI: 10.37801/ajad2020.17.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of the COVID-19 Pandemic on Agricultural Production in Southeast Asia: Toward Transformative Change in Agricultural Food System

Abstract: How will the COVID-19 pandemic affect the agriculture sector in Southeast Asia? Clearly, any disruptions in the agricultural food systems would create supply and demand shocks that would impact on the agriculture sector's immediate and long-term economic performance and food security contribution. Overall, the COVID-19 pandemic during the first quarter of year 2020 is estimated to result in 3.11 percent or 17.03 million tons reduction in aggregate volume of agricultural production in Southeast Asia due to decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 1 publication
1
63
0
1
Order By: Relevance
“… Hossain (2020) showed that in the short, medium and long term, food safety challenges due to COVID-19 have varied among the member countries of the Asian Productivity Organization. Similarly, Gregorioa and Ancog (2020) concluded that, in Southeast Asia, the experience of this pandemic should be drawn upon to ensure food safety by treating it as a coordinated problem between the public and private sectors. In a study carried out in Bangladesh, Nur-E-Alam et al (2020) recommended meeting citizens’ food needs with local supplies to minimise the risk of impacts on food safety.…”
Section: Resultsmentioning
confidence: 99%
“… Hossain (2020) showed that in the short, medium and long term, food safety challenges due to COVID-19 have varied among the member countries of the Asian Productivity Organization. Similarly, Gregorioa and Ancog (2020) concluded that, in Southeast Asia, the experience of this pandemic should be drawn upon to ensure food safety by treating it as a coordinated problem between the public and private sectors. In a study carried out in Bangladesh, Nur-E-Alam et al (2020) recommended meeting citizens’ food needs with local supplies to minimise the risk of impacts on food safety.…”
Section: Resultsmentioning
confidence: 99%
“…Taking Southeast Asia as an example, the disruptions of supply chains could translate into huge demand shocks, for the first quarters of year 2020 only, a 3% decline or 17.03 million tons reduction in aggregate volume of production that estimate affecting 100.77 million individuals were recorded. This economical lost is equivalence to 1.4% decrease of GDP or USD 3.76 billion ( Gregorioa and Ancog, 2020 ). Shortage at the supermarkets is not caused by a disruption in the global supply chain but only a temporal shortage at retailer supply chains due to panic buying by the consumers (Voegele, 2020) which is quickly resolved at almost all supermarkets across the globe with stabilised supply ( OECD, 2020 ).…”
Section: Economic Impact Of Pandemics On the Food And Agricultural Sementioning
confidence: 99%
“…Seventeen studies were collected under the AGRI2 category (Alekseev, Ruschickaya, & Yurchenko, 2020; Barcaccia et al, 2020; Blay‐Palmer et al, 2020; Christiaensen et al, 2020; Deaton & Deaton, 2020; Dupouy & Gurinovic, 2020; Fanzo et al, 2020; Gregorioa & Ancog, 2020; Hossain, 2020; Kennedy, Jafari, Stamoulis, & Callens, 2020; Ma, Peng, Soon, et al, 2020; Mausch et al, 2020; Popovic et al, 2020; Rowan & Galanakis, 2020; Savary et al, 2020; Singh et al, 2020; Sperling et al, 2020).…”
Section: Analysis and Findingsmentioning
confidence: 99%
“…Domestic food supply was significantly affected by labor shortages, disruption of distribution systems, loss of income (Savary et al, 2020; Singh et al, 2020) as well as the massive loss of agricultural products that were impossible to transfer due to restrictive measures imposed by governments (Ma et al, 2020). For example, the food demand shocks in Southeast Asia were huge due to disruptions in the food supply chain, equivalent to a 1.4% decrease in GDP (Gregorioa & Ancog, 2020). The effects of COVID‐19 on countries' food supply chain under civil unrest, political isolation, or underinvestment in public health are adverse.…”
Section: Analysis and Findingsmentioning
confidence: 99%